Purchase Decision Of Disabilities Product: Dilemma Between Product Quality To Humanitarian Spirit - Epriliyana, Nike Norma (Majalah Ilmiah DIAN ILMU, 2024)
Purchasing decision making has a unique and diverse process. Products created by people with disabilities are no exception. In general, the purchasing decision process begins with (a) Need recognition, (b) Information search, (c) Alternative evaluation, (d) Purchase, (e) Post purchase behaviour. However, in certain unique cases, the purchasing decision process does not go through the general purchasing decision process. One of them is the purchasing decision process for disability products. This research explores the purchasing decision process for disability products. The focus of the research is on exploring the steps of consumers in purchasing disability products to post purchase behaviour. The research was conducted through a qualitative descriptive approach. Data collection techniques were carried out by interview and observation. The sampling technique used purposive sampling and snowball sampling. Data analysis and interpretation procedures consist of data collection; data reduction; data display; conclusion and verification. Thei nformants are consumers who decide to buy disability products at exhibition or bazaar or expo that specifically sell products made by disabilities. The results show that there are 4 (four) purchasing decision processes for disability products, namely (1) the purchasing decision process based on product quality; (2) the purchasing decision process based on price; (3) the purchasing decision process based on desire; (4) the purchasing decision process based on humanitarian spirit.